Some Kind of Bond - Cavarzan, Chiara (Journal of Anthropological Films, 2021)
Some Kind Of Bond is a film about a cemetery: a quiet and lonely place filled with life and memories. We observe the casual and the diligent visitors; we talk with them about their thoughts on death, loss and grief. Some of them decide to invite us to their homes and together we go on an emotional journey through different personal experiences: the loss of a child, a grandparent and a mother.